Studi Gaya Hambat GJB Pada Variasi Luas Permukaan Kertas Cupcake dengan Analisis Video & Python - Nurfitni, Diana; Pramudya, Yudhiakto (UNIVERSITAS INDRAPRASTA PGRI, 2023)
The surface area of an object influences the drag force. The character of changes in the drag force of the cupcake paper during free fall motion will be investigated through experiments and analytics. Variations in the surface area of the cupcake paper were carried out to determine its effect on the drag force. Tracker video analysis and Python software were used in this study. With video analysis techniques, we can obtain data regarding the travel time and speed of the cupcake paper during free fall. Next, Python software is used to analyze the data to produce the drag force constant value. The drag force coefficients are 0.00014, 0.00019, 0.0018, and 0.0022 at the bottom surface diameter of the cupcake paper 2.95 cm, 4.22 cm, 5.05 cm, and 5.13 cm. The greater the bottom surface area of the cupcake paper, the higher the coefficient of drag produced, which can result in a greater drag force